Author’s Reply to Peronard and Mayntz: “SGLT2 Inhibitors, and How They Work Beyond the Glucosuric Effect” (2024)
We would like to express our sincere gratitude to the reviewers for their thoughtful and detailed comments on our article. We hope that our responses adequately address their concerns and that this exchange of ideas contributes to a broader understanding of the topic. We believe that letters to the editor serve as valuable platforms for scholarly discussion and the dissemination of knowledge. We encourage continued dialogue and debate on this important subject.